The vestibular body: Vestibular contributions to bodily representations. Issue 1 (17th February 2016) - Ferrè, Elisa Raffaella; Haggard, Patrick
ABSTRACT: Vestibular signals are integrated with signals from other sensory modalities. This convergence could reflect an important mechanism for maintaining the perception of the body. Here we review the current literature in order to develop a framework for understanding how the vestibular system contributes to body representation. According to recent models, we distinguish between three processes for body representation, and we look at whether vestibular signals might influence each process. These are (i) somatosensation, the primary sensory processing of somatic stimuli, (ii) somatoperception, the processes of constructing percepts and experiences of somatic objects and events and (iii) somatorepresentation, the knowledge about the body as a physical object in the world. Vestibular signals appear to contribute to all three levels in this model of body processing. Thus, the traditional view of the vestibular system as a low-level, dedicated orienting module tends to underestimate the pervasive role of vestibular input in bodily self-awareness.